Cercospora kikuchii aislada en la provincia de Santa Fe (Argentina): variabilidad genética y producción de cercosporina in vitro - González, Ana María (2008)
The aims of the present study were to analyze the genetic variability of Cercospora kikuchii isolates and the in vitro cercosporin production, of these isolates obtained from soybean at the central-northern region of Santa Fe province (Argentina). Also the relationship between RAPD profiles and toxin production was also assessed. The strain C. kikuchii NBRC 6711 and 13 soybean isolates with symptoms of leaf blight were tested. Cercosporin production was analyzed by growing the fungus on Potato Dextrose Agar, extracting the toxin in alkaline medium and determining its concentration by spectrophotometry. The population of C. kikuchii studied showed variability, both genotypically, nine different groups were encountered, and have the ability to produce cercosporin. No relationship was found between toxin production and the RAPD profiles.